144 Specialist Palliative Care Inreach to the Emergency Department. (14th March 2023) - Gillon, Suzie; Jacob, Faith; Fairbairn, Lorna; Nunn, Katy; Higgins, Sarah
Abstract : Background: Emergency departments (EDs) are under unprecedented pressure due to multiple factors including: a rising and ageing population; rising bed occupancy in hospitals; reduced capacity in social care and community services and high levels of staffing attrition. Attendance of patients known to, and suitable for, palliative care in the last year of life is common1, 2, 3. This project sought to assess the impact of a proactive Specialist Palliative care (SPC) in-reach service into the ED within current resource. Methods: From November 2021 a SPC doctor and Clinical Nurse Specialist (CNS) visited the ED every weekday morning following the ED departmental handover meeting, where patients were identified as 'may benefit from palliative care input'. Patients were reviewed in the department, verbal advice given to the ED team or followed up later in admission. Results: Referrals from ED to SPC increased from 10 in the 6 months pre-project to 60 in the following 6 months. Patients were often elderly (mean age 76, range 42–101); with a high proportion of non-malignant diagnoses (58%), many from 24 hour care (26%) and with a poor prognosis (80% of first 50 patients had died within the study period). SPC input included: advance care planning; symptom management and prescribing; supporting dying patients in the ED; goals of care decisions; assisting with challenging conversations; enabling rapid discharge, and referral to community and hospice services. High levels of satisfaction with the service were found when surveying ED and SPC staff, although the increased number of referrals has implications for SPC workload. Ongoing work aims to further define most useful SPC impact, and develop stronger links with Acute Medical teams to best influence hospital admissions. (Further up to date results will be supplied at PCC if submission is successful)